Chinese Herbal Medicine Effectively Prolongs the Overall Survival of Pancreatic Cancer Patients: A Case Series. (February 2019) - Wong, Wendy; Chen, Bing Zhong; Lee, Allyson Kin Yan; Chan, Adrian Ho Cheung; Wu, Justin Che Yuen; Lin, Zhixiu
Background and Aims: Pancreatic cancer has the lowest survival rate of all cancers (4%), and it accounts for 1.9% of new cancer cases in Hong Kong. Combined treatment with Chinese herbal medicine (CHM) and Western medicine has yielded promising results, leading to improved prognosis and overall survival. This retrospective case series aimed to illustrate the improved survival and quality of life outcomes of pancreatic cancer patients administered CHM based on traditional Chinese medicine theory.Methods: To investigate the effectiveness of CHM in prolonging overall survival, 182 patients diagnosed with pancreatic cancer who received CHM treatment were observed from 2005 to 2015.Results: One hundred eighty-two pancreatic cancer patients were treated with CHM; 21 patients died. The mean and median survival of these patients were 29.6 and 15.2 months, respectively; the 1-year survival rate was 76% (range = 4 months to 9 years). These results are better than those reported in patients treated with Western medicine, suggesting the need for further study of CHM.Conclusion: A superior clinical outcome may be obtained with CHM treatment. The case series illustrates the potential benefits and safety issues of CHM in pancreatic cancer patients that could be relevant for developing strategies to increase individualization of pancreatic cancer treatment and improve survival. This study may facilitate interprofessional communication and improved clinical management of pancreatic cancer patients.